Epibiotic barnacles of sea turtles as indicators of habitat use and fishery interactions: An analysis of juvenile loggerhead sea turtles, Caretta caretta, in the western Mediterranean. (December 2019) - Ten, S.; Pascual, L.; Pérez-Gabaldón, M.I.; Tomás, J.; Domènech, F.; Aznar, F.J.
Highlights: Lepas hillii and Conchoderma virgatum attachment indicates oceanic habitat use by sea turtles. Chelonibia testudinaria presence signals neritic habitat use by sea turtles. C. virgatum usually attached postmortem, denoting death in oceanic habitat. L. hillii occurrence suggests stays in oceanic waters at least several weeks before collection. C. testudinaria tags visits to neritic waters several months before collection. Abstract: Sea turtles exploit a variety of habitats during their lifetime and are thus exposed to a number of anthropogenic threats, including interaction with fisheries. Mitigating this impact requires determining patterns of habitat use by turtles, which largely relies on data from marked individuals. We investigated the use of epibiotic barnacles as a cost-effective method to ascertain habitat use by sea turtles, choosing the juvenile loggerhead sea turtles ( Caretta caretta ) in the western Mediterranean as a model. A total of 200 turtles collected in the central Spanish Mediterranean between 1990 and 2017 were examined for epibionts: 25% were accidentally captured by pelagic longliners, 19% by neritic gears, and 56% were stranded by unknown causes. Gut contents of 80 deceased turtles were also examined to infer the habitat(s) exploited by the turtles 1–2 weeks prior to death. We collected 16, 652 barnacles of 13 species. Barnacle assemblages of turtles captured by longliners, or having oceanic prey only, were dominated by Lepas hillii and Conchoderma virgatum, whereas the turtles captured by neritic fisheries, or having neritic prey, had significantly higher loads of Chelonibia testudinaria . A canonical discriminant analysis based on barnacle abundance correctly assigned 80.5% of caught turtles to the responsible fishery, and predicted a nearly identical assignation to fishery of stranded turtles. The estimated age distribution for C. virgatum was unimodal, and many individuals were inferred to have attached postmortem, thus tracing the habitat where turtles died. The age distribution for L. hillii was bimodal, and the old individuals informed on stays of turtles in oceanic waters of at least few weeks prior to death. Finally, C. testudinaria settled on live turtles and were comparatively older, marking the stay of turtles in neritic waters several months before death. In summary, data on presence and estimated age of these 3 barnacle species not only shed much light on habitat where turtles died, but also helped to trace movements and residence times in each habitat. We encourage researchers to include barnacles as a complementary source of data on habitat use of sea turtles.